Adults video gaming: Key competences for a globalised society. (November 2019) - Alonso-Díaz, Laura; Yuste-Tosina, Rocío; Mendo-Lázaro, Santiago
Abstract: Is it possible that by playing video games adults can develop key competences that may prove beneficial in dealing with the new challenges of 21st-century society? The present study identifies the profile of adult video gamers and defines the characteristics of the games they choose to play. It also examines the way and with what type of video games adults perceive that key competences are developed. From a quantitative perspective, the questionnaire on video games and adult education (QVAD) (Alonso and Yuste, 2015) was applied to a sample of 404 subjects. The results confirmed that adult video gamer, while playing, also learns and develops key competences. Role-playing games are those most closely linked to the development of hard (technical, practical and mechanical) and soft skills (personality traits) for globalised society. In order to favour video games of interest to adults, they should be allowed to choose different levels of difficulty and promote individual decision-making, commitment and responsibility. Information and motivation regarding video games should be reoriented, especially in the case of women with secondary and higher education and older people, who choose cognitive and strategy video games out of concern for their cognitive development, when role-playing would really respond better to their needs. Highlights: Playing video games promotes competence acquisition in adults. Adults with higher education under stress play on a console as an escape valve. Older adults are interested in strategy and cognitive games. Role-play video games favour competences for a globalised society. Hard and soft skills are developed through contextualised and personalised video games.